1992
DOI: 10.1029/92je00344
|View full text |Cite
|
Sign up to set email alerts
|

Mars Observer magnetic fields investigation

Abstract: The Mars Observer magnetic fields investigation will provide fast vector measurements of the Martian magnetic field over a wide dynamic range. The fundamental objectives of this investigation are (1) to establish the nature of the magnetic field of Mars, (2) to develop appropriate models for its representation, which take into account the internal sources of magnetism and the effects of the interaction with the solar wind, and (3) to map the Martian crustal remanent field to a resolution consistent with the Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 40 publications
1
91
0
Order By: Relevance
“…Therefore this interaction is similar in many ways to that of Venus or comets (Acuña et al, 1998). The MGS measurements have provided us a clear identification of the boundaries such as the bow shock (BS) and the magnetic pile-up boundary (MPB), located downstream the bow shock and upstream the ionopause.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore this interaction is similar in many ways to that of Venus or comets (Acuña et al, 1998). The MGS measurements have provided us a clear identification of the boundaries such as the bow shock (BS) and the magnetic pile-up boundary (MPB), located downstream the bow shock and upstream the ionopause.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the absence of a global magnetic field of the internal origin (Acuña et al, 1998), the upper atmosphere and the dayside ionosphere interact directly with the solar wind plasma. The Magnetometer/Electron reflectometer (MAG/ER) experiment on board Mars Global Surveyor (MGS) spacecraft has revealed the presence of crustal magnetic fields ).…”
Section: Introductionmentioning
confidence: 99%
“…Among other important results, the measurements made by the magnetometer (MAG) on board the Mars Global Surveyor (MGS) spacecraft [Acuña et al, 1992] showed that Mars does not have a significant intrinsic magnetic field [Acuña et al, 1998]. As a consequence, there is a direct interaction between the magnetized solar wind (SW) and the atmosphere/ionosphere of the planet.…”
Section: Introductionmentioning
confidence: 99%
“…Mars' magnetic field has been exhaustively measured between 100 and 440 km altitude by Mars Global Surveyor (Acuña et al, 1998;Connerney et al, 2005;Morschhauser et al, 2014). These data show that the magnetic anomalies of the martian crust are up to 20 times higher than those of the Earth (Scott and Fuller, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…A second objective is the magnetic investigation of these sites and their implication as terrestrial analogues of Mars. A further objective is the potential of high-resolution mapping to show the lowest magnetic contrasts in the terrain and their correlation with the distinct magnetic carriers responsible for their signatures (Acuña et al, 1998;Connerney et al, 2005;.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%